Buckling of elastically restrained cantilever wall with free edge stiffening - Szychowski, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The issue of the stability loss in a compressed wall of a thin-walled member with an open cross section was reduced to the buckling analysis of the cantilever wall. The wall was unilaterally elastically restrained against rotation. The stiffening of the free edge of the wall was susceptible to deflection. The plate deflection functions and stiffenings that allow the modelling of boundary conditions on both longitudinal edges were proposed. Graphs of buckling coefficients for different indexes of the elastic restraint of the supported edge and different geometries of the edge stiffening were determined.